THE LAW ENFORCEMENT AGAINST AN ILLEGAL ONLINE LOANS PLATFORM - Khaq, Ifan Eldin; Hidayat, Ahmad (jfpublisher, 2022)
Law is the regulation of norms and sanctions created with the purpose of regulating human behavior to maintain order, uphold justice, and prevent chaos. Each country has its own legal system, which differs from others, including Indonesia. Indonesia is a state of law, as stated in Article 1, Paragraph 3 of the 1945 Constitution. This research uses a library legal research method, which is conducted using a descriptive approach to analyze social phenomena within the community through a balanced qualitative perspective. In the Financial Services Authority Online system, despite being supervised by the OJK, online loan services still pose risks, such as high interest rates and concerns over data security, as personal information remains vulnerable to leaks. Customer data is highly susceptible to breaches and uncontrolled distribution. The enforcement of laws regarding illegal online financial services, such as law enforcement measures and dispute resolution, has not yet fulfilled the principles of legal protection and fairness for borrowers using online monetary services registered under the Monetary Service Authority Regulations.